Seismic analysis of nailed soil slope considering interface effects. Issue 100 (September 2017) - Chavan, Dhanaji; Mondal, Goutam; Prashant, Amit
Abstract: Natural soil slopes are often reinforced with nails to stabilize them against earthquake loading. Although pseudo-static method is widely used in designing such slopes; it fails to provide important information such as deformation of slope, effect of soil-nail interface etc. A 2-D finite element model of typical nailed slope has been prepared during this study using OpenSees to perform seismic analysis with due consideration to soil nonlinearity, pressure dependency of soil and separation-sliding at soil-nail interface. It is found that the soil-nail interface modelling can significantly influence the permanent deformation of slope after seismic event. The overburden pressure on the nail varies significantly during the earthquake loading and the variation is more when sliding and separation is allowed at the soil-nail interface. It is also found that the model with fixed interface leads to a perception of reinforced soil acting as a relatively rigid block, which results into an unconservative design from overall deformation perspective. Highlights: Deformation of slope is significantly more when sliding and separation is allowed at the soil-nail interface (SS). The crest displacement is found to be much greater when separation and sliding is allowed at the soil-nail interface (SS). Failure surface is observed to be close to that assumed in German method. Overburden pressure on the nail is found to have large variation during the shaking. Variation of overburden pressure is more in SS case.